Palliative care provision for people living with heart failure: The Geneva model - Hentsch, Lisa; Sobanski, Piotr Z.; Escher, Monica; Pautex, Sophie; Meyer, Philippe (Frontiers in Cardiovascular Medicine, 2022)
As life expectancy rises and the survival rate after acute cardiovascular events improves, the number of people living and dying with chronic heart failure is increasing. People suffering from chronic ischemic and non-ischemic heart disease may experience a significant limitation of their quality of life which can be addressed by palliative care. Although international guidelines recommend the implementation of integrated palliative care for patients with heart failure, models of care are scarce and are often limited to patients at the end of life. In this paper, we describe the implementation of a model designed to improve the early integration of palliative care for patients with heart failure. This model has enabled patients to access palliative care when they normally would not have and given them the opportunity to plan their care in line with their values and preferences. However, the effectiveness of this interdisciplinary model of care on patients’ quality of life and symptom burden still requires evaluation.